The role of science, technology and innovation for sustainable development agenda - Hoa, Nguyen Viet (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
Science, technology and innovation (STI) are key means of implementation for the 2030 Agenda for Sustainable Development. In the context of the Fourth Industrrial Revolution the role of science, technology and innovation policy-making is increasingly important. This paper addres three main contents: (i) Theory of making the STI policy; (ii) The context of STI policy-making; and (iii) Framework of STI policy-making. Code: <span style="text-align: left; color: #000000; text-transform: none; text-indent: 0px; letter-spacing: normal; font-size: 14px; font-variant: normal; font-weight: 400; text-decoration: none; word-spacing: 0px; white-space: normal; orphans: 2; -webkit-text-stroke-width: 0px; background-color: #ffffff;">20050501